2009
DOI: 10.1523/jneurosci.3992-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Promote Axon Regeneration with Concurrent Neurotoxicity

Abstract: Activated macrophages can promote regeneration of CNS axons. However, macrophages also release factors that kill neurons. These opposing functions are likely induced simultaneously but are rarely considered together in the same experimental preparation. A goal of this study was to unequivocally document the concurrent neurotoxic and neuroregenerative potential of activated macrophages. To do so, we quantified the length and magnitude of axon growth from enhanced green fluorescent protein-expressing dorsal root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
161
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(168 citation statements)
references
References 66 publications
5
161
0
2
Order By: Relevance
“…Investigations have led to opposing conclusions with respect to their beneficial versus detrimental roles in SCI and SCIassociated complications, however. 4,[36][37][38] In contrast, our earlier and current studies consistently support the notion that TLR9 antagonism after SCI is beneficial and promotes recovery of sensory and autonomic functions, as reflected by improved thermal hypersensitivity and bladder voiding, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…Investigations have led to opposing conclusions with respect to their beneficial versus detrimental roles in SCI and SCIassociated complications, however. 4,[36][37][38] In contrast, our earlier and current studies consistently support the notion that TLR9 antagonism after SCI is beneficial and promotes recovery of sensory and autonomic functions, as reflected by improved thermal hypersensitivity and bladder voiding, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…The innate immune response in the central nervous system (CNS) is mediated by resident microglia, astrocytes, and infiltrating macrophages and neutrophils that can release numerous anti-and pro-inflammatory cytokines, chemokines, growth factors, and other signals. Although some of these factors are toxic to neurons, inflammation has been shown to promote axon regeneration and/or enhance cell survival in the optic nerve (5-9), dorsal roots (10,11), and spinal cord (12,13,14) after injury. In the optic nerve, a CNS pathway that normally shows little capacity to regenerate when injured, peripheral nerve implants into the eye, lens injury, or intraocular injections of zymosan all cause macrophages to enter the eye and stimulate retinal ganglion cells (RGCs) to regenerate lengthy axons beyond the injury site (7,8,15).…”
mentioning
confidence: 99%
“…Based on their function as receptors for "danger signals" (9), TLR expression in glial cells is implicated in various "sterile" neurological disorders including mouse cerebral ischemia/reperfusion injury (10,11), spinal cord injury (12), and axonal transection (13). We have also reported that TLR2 plays a critical role in nerve injury-induced spinal cord glial activation and subsequent pain hypersensitivity (14), and traumatic brain injury (15).…”
mentioning
confidence: 99%